2020
DOI: 10.17509/jpjo.v5i2.25466
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Screening: An Early Detection of The Student Injury Risk in Sport Class

Abstract: Physical Education class is one of the solutions taken by regional schools to improve achievements in sports. The process of recruiting physical education class students has mostly conducted by using  the talent scouting test method which consists of physical test and skill test. However, the implementation of sport injury detection test using Functional Movement Screening (FMS) is still insignificant. The purpose of this study was to identify the student risk of injury in physical education class by using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
9
0
4
Order By: Relevance
“…Of the available studies, some include both boys and girls [32,40,41,44 Of the studies that included both boys and girls, some studies have not reported sex differences in the FMS [57,77,78,82]. Other studies have reported no significant differences in the FMS scores between boys and girls [36,38,41,44,48,49,58,62,63,76,81,83,86,87,[89][90][91]93,99,103,110].…”
Section: Sex and Age Differences In The Performance On The Fmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the available studies, some include both boys and girls [32,40,41,44 Of the studies that included both boys and girls, some studies have not reported sex differences in the FMS [57,77,78,82]. Other studies have reported no significant differences in the FMS scores between boys and girls [36,38,41,44,48,49,58,62,63,76,81,83,86,87,[89][90][91]93,99,103,110].…”
Section: Sex and Age Differences In The Performance On The Fmsmentioning
confidence: 99%
“…Although there is a plethora of research on the use of the FMS in adults, there is growing scientific evidence indicating the use of the FMS in youth. Studies to date have been performed in the United States, Canada [ 42 , 43 ], Hungary and Germany [ 44 , 45 ], Italy [ 46 ], Moldova [ 38 ], countries of the UK [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Ireland [ 58 , 59 ], Poland [ 60 , 61 , 62 , 63 , 64 ], Slovakia [ 65 ], Iran [ 66 , 67 , 68 ], Turkey [ 69 , 70 , 71 , 72 , 73 , 74 ], Japan [ 75 ], China [ 76 , 77 ], Thailand [ 32 ], Taiwan [ 78 , 79 , 80 ], Korea [ 81 ], Indonesia [ 82 ], Croatia [ 40 , 41 , 83 , 84 ], Brazil [ 85 ], Portugal [ 86 ], Spain [ 87 , 88 , 89 , 90 …”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…Karena perkembangan pikiran anak sesungguhnya dilandasi gerakan dan perbuatan, oleh karena itu anak harus diberikan kesempatan untuk bergerak dan berbuat pada objek yang nyata, karena pada dasarnya setiap anak mempunyai motifasi untuk berprestasi. Sedangkan Pemanduan adalah proses, cara, atau perbuatan dalam memimpin atau melatih mendidik, mengajari dan sebagainya supaya dapat melakukan pekerjaan sendiri (Syafei et al, 2020). Berdasarkan pengertian tersebut di atas, dapatlah dikemukakan bahwa pengertian pemanduan bakat adalah proses dalam usaha untuk menemukan atau mendapatkan tanda-tanda atau dasar yang dimiliki oleh seseorang seperti kepandaian, keterampilan, sifat dan pembawaan yang dibawa sejak lahir yang dilakukan dengan jalan memprediksi atau memperkirakan bahwa seseorang itu mempunyai peluang dalam suatu cabang olahraga tertentu untuk dibina dan dikembangkan menjadi atlet yang memiliki potensi tinggi, sehingga diharapkan akan berhasil di dalam mengikuti latihan-latihan dan mencapai prestasi puncak.…”
Section: A Definisi Bakatunclassified
“…Program latihan yang dijalankan dengan baik juga tidak hanya untuk meningkatkan performa atlet, akan tetapi juga dapat membantu atlet untuk dapat terhindar dari berbagai kemungkinan terjadinya cedera (Syafei et al, 2020). Pada usia remaja, atlet tenis berpotensi mengalami berbagai cedera karena tidak menerapkan program latihan dengan tepat (Budi, Agustan, et al, 2020).…”
unclassified